2016
DOI: 10.1007/s10162-016-0566-8
|View full text |Cite
|
Sign up to set email alerts
|

The Cervical Vestibular-Evoked Myogenic Potentials (cVEMPs) Recorded Along the Sternocleidomastoid Muscles During Head Rotation and Flexion in Normal Human Subjects

Abstract: Tone burst-evoked myogenic potentials recorded from tonically contracted sternocleidomastoid muscles (SCM) (cervical VEMP or cVEMP) are widely used to assess the vestibular function. Since the cVEMP response is mediated by the vestibulo-collic reflex (VCR) pathways, it is important to understand how the cVEMPs are determined by factors related to either the sensory components (vestibular end organs) or the motor components (SCM) of the VCR pathways. Compared to the numerous studies that have investigated effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…We compared the characteristics of the SCM cVEMP recorded using the standard clinical arrangement with that recorded from SPL using a simpler alternative posture. Previous work has demonstrated that the SCM cVEMP consists of a biphasic positive–negative response with peak latencies of ~ 13 and 23 ms, respectively, although more recent work has demonstrated variability in polarity depending on electrode position (Wei et al ., ; Ashford et al ., ; Rosengren et al ., ). IM recordings confirm that the p13 and n23 responses relate to a reduction and subsequent rebound of SCM activity, respectively (Colebatch & Rothwell, ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We compared the characteristics of the SCM cVEMP recorded using the standard clinical arrangement with that recorded from SPL using a simpler alternative posture. Previous work has demonstrated that the SCM cVEMP consists of a biphasic positive–negative response with peak latencies of ~ 13 and 23 ms, respectively, although more recent work has demonstrated variability in polarity depending on electrode position (Wei et al ., ; Ashford et al ., ; Rosengren et al ., ). IM recordings confirm that the p13 and n23 responses relate to a reduction and subsequent rebound of SCM activity, respectively (Colebatch & Rothwell, ).…”
Section: Discussionmentioning
confidence: 98%
“…Note as well that SCM is also compartmentalized into multiple subvolumes with different attachments (Kamibayashi & Richmond, 1998). Recent work has shown that cVEMP waveform polarity on SCM can be inverted if the active electrode in the standard belly-tendon montage is placed outside of the conventional recording zone (Wei et al, 2013;Ashford et al, 2016;Rosengren et al, 2016).…”
Section: Emg Electrodes and Signal Processingmentioning
confidence: 99%
“…Previous research has shown that the amplitude of the cVEMP is influenced by how an individual is asked to produce SCM contraction. For example, Ashford et al 26 evaluated the cVEMP from subjects who produced SCM contraction by lifting their heads toward the midline as well as turning their heads and elevating their heads from a supine position. They found that at certain locations along the SCM muscle, rotating and elevating the head to produce SCM contraction resulted in larger cVEMP amplitudes as compared with flexion of the head toward the midline.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical VEMPs are predominantly ipsilateral, but may sometimes have a contralateral component ( Colebatch and Rothwell, 2004 ; Ashford et al, 2016 ). Use of binaural stimuli limited variation due to any between participant difference in the extent of contralateral activity, because ipsilateral and contralateral components of the VEMP from each ear were present at both SCM muscles.…”
Section: Methodsmentioning
confidence: 99%